PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata) PADA BERBAGAI DOSIS PUPUK ORGANIK - Jurhana, Jurhana; Made, Usman; Madauna, Ichwan (AGROTEKBIS, 2017)
This research aims to determine the growth and yield of sweet corn plants at various doses of organic fertilizer. The research was conducted in New Village, Palu Barat Sub-district, Palu City, which lasted from May to July 2013. This research uses Randomized Block Design, consisting of 6 treatments, namely A = organic fertilizer, B = organic fertilizer 5 ton/ha, C = organic fertilizer 10 ton/ha, D = organic fertilizer 15 ton/ha, E = organic fertilizer 20 ton/ha and F = organic fertilizer 25 ton/ha. Each treatment was repeated three times as a group of 36 plants. Data of observation result were analyzed by Variance (F-Test), if the result of variance analysis showed the real difference then continued test of real honest difference (BNJ). The results showed that the application of organic fertilizer 15 ton/ha in sweet corn plants had the same effect as inorganic fertilizer dose 300 kg urea/ha + 100 kg SP-36/ha + 100 kg KCl/ha. Key Words : Organic fertilizers, Sweet corn.